Metal–metal bonding in biscycloheptatrienyl dimetal compounds of the second‐row transition metals. Issue 12 (23rd March 2017) - Zhang, Zhihui; Feng, Xuejun; Chen, Qun; He, Mingyang; Xie, Yaoming; Bruce King, R.; Schaefer, Henry F.
Abstract: Density functional theory has been used to examine the dimetallocene‐like dicycloheptatrienyl dimetal compounds of the second‐row transition metals (C7 H7 )2 M2 (M = Ru, Tc, Mo, Nb, Zr). The lowest energy (C7 H7 )2 Mo2 structure is a coaxial structure with terminal η 7 C7 H7 rings, whereas the lowest energy (C7 H7 )2 M2 structures (M = Ru, Tc, Nb, Zr) are perpendicular structures with bridging η 4, η 4 C7 H7 rings except for the perpendicular (η 4, η 3 C7 H7 )2 Ru2 structure. The metal–metal bond orders in the (C7 H7 )2 M2 structures (M = Ru, Tc, Mo, Nb), as determined by analysis of their frontier molecular orbitals, suggest preferred 16‐ rather than 18‐electron configurations for the central metal atoms. Thus, in the coaxial (η 7 C7 H7 )2 M2 structures the formal bond orders are two for M = Tc and three for M = Mo. For the perpendicular structures both (η 4, η 3 C7 H7 )2 Ru2 and (η 4, η 4 C7 H7 )2 Tc2 have 16‐electron configurations with metal–metal single bonds owing to the different modes of bonding of the bridging C7 H7 rings in the two structures. For the (C7 H7 )2 Zr2 system the perpendicular structure has a formal ZrZr double bond and the coaxial structure has a very long (∼3.5 Å) ZrZr bond indicating only 12‐ to 14‐electron configurations for the zirconium atoms. Abstract : Second‐row transition metals complexes (C7 H7 )2 M2 are explored in search for interesting examples of high order metal–metal multiple bonding. The lowest energy (C7 H7 )2 Mo2 structure is a coaxial structure with terminal η 7 C7 H7 rings whereas the lowest energy (C7 H7 )2 M2 structures (M = Ru, Tc, Nb, Zr) are perpendicular structures with bridging C7 H7 rings. The metal–metal bond orders in the (C7 H7 )2 M2 structures suggest preferred 16‐ rather than 18‐electron configurations for the metal atoms.